Effects of Plasmid Curing on Multi-Drug-Resistant Salmonella from Poultry Litter in Nasarawa Town, Nasarawa State, Nigeria - Yakubu Aliyu; Chrinius Hammuel; Ajang Yakubu Abubakar; Justina Adegba (UMYU Journal of Microbiology Research, 2025)
Study’s Excerpt: